The Influence of Project-Based Learning Learning Model and Educability Motor Level of Fundamental Motor Skill Students in Class III Elementary School Students - Hilmy Aliriad (International Conference on Science, Education, and Technology, 2021)
Model Learner’s Project-Based learning and level Motor Educability can upgrade Motion elementary students (Fundamental Motor Skill). The purpose of this study is to get the implications of the Project- based learning model of learning so that students are not focused on the teacher, but can choose their projects facilitated by the teacher. This study uses a random control group pretest and post-test design experimental method. The population in the study was 86 people, with the number of samples until treatment group I was 24 people given PjBL learning models with high motor educability, treatment group II was 24 people given with low motor education. The test used is a fundamental motor skill test to measure students' basic movements. This study concludes that the Project-Based Learning Model with the level of motor educability has a significant effect on the basic movements of students (Fundamental Motor Skill).